2005
DOI: 10.1207/s15327027hc1701_5
|View full text |Cite
|
Sign up to set email alerts
|

Sensation Seeking and Adolescent Drug Use: The Mediating Role of Association With Deviant Peers and Pro-Drug Discussions

Abstract: In this study, I examined direct and indirect influences of sensation seeking, a personality trait, on adolescent drug use. I hypothesized that some or even most of the contribution of sensation seeking to drug use by adolescents is mediated through association with deviant peers and communication with peers that is favorable toward drug use. I examined the role of additional risk or protective factors in facilitating or impeding association with deviant peers, pro-drug communication, and marijuana use as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
83
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 30 publications
12
83
1
2
Order By: Relevance
“…Deviant peer affiliation predicted subsequent marijuana use, and the growth, but not the level, of social images predicted subsequent marijuana use. As predicted, a mediated pathway from early sensation seeking to later marijuana use through affiliation with deviant peers was confirmed (Donohew, Hoyle, et al, 1999;Yanovitzky, 2005). However, contrary to our hypothesis, social images did not mediate the influence of sensation seeking.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Deviant peer affiliation predicted subsequent marijuana use, and the growth, but not the level, of social images predicted subsequent marijuana use. As predicted, a mediated pathway from early sensation seeking to later marijuana use through affiliation with deviant peers was confirmed (Donohew, Hoyle, et al, 1999;Yanovitzky, 2005). However, contrary to our hypothesis, social images did not mediate the influence of sensation seeking.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have established that sensation seeking, deviant peer affiliation, and positive evaluation of substances are risk factors for marijuana use, and also that affiliating with deviant peers may mediate effects of sensation seeking (Yanovitzky, 2005;Zuckerman, 1994). The present study advanced the understanding of these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Kandel and Jessor [19] suggest that substance use progression may commence from a more complex development sequence of activities including other key behaviors and experiences such as joining a gang, dropping out of school, etc. Yanovitzky [20] demonstrated that sensation seeking, some protective factors (such as religiosity, positive family relationship, school performance) and risk factors (such as unsupervised time with peers, frequency of school absences) contributed to association with deviant peers, which led to pro-drug discussions, and finally, to a greater intention to use drugs. Multiple pathways (both direct and indirect) explain the association between personality factors and risk behaviors.…”
Section: Interrelationships Between Different Systemsmentioning
confidence: 99%
“…High sensation seekers also tend to underestimate the risk associated with health behaviors such as cigarette smoking, drug use, and alcohol consumption, and thereby engage in it more as compared to their low sensation seeking counterparts [22]. High sensation seekers also tend to have friends who engage in similar risk behaviors [20].…”
Section: Sensation Seeking Delinquent Behaviors and Adolescent Cigamentioning
confidence: 99%
See 1 more Smart Citation